Determination of changes in the coordinates of zodiac stars using an astronomical application (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
In this scientific report, changes in the horizontal and equatorial coordinates of the largest stars of the zodiacal constellations, stars α, in the years 1000-1600 and 2000 were determined with the help of an astronomical application. Azimuth stars Alshira changed to A=1010011. Azimuth stars Hamal changed to A=1330151. Azimuth stars Aldebaran changed to A=740141. Azimuth stars Castor changed to A=240221. Azimuth zvjedi Akubens changed to A=270161. Azimuth stars Regula changed to A=280191. Azimuth stars Spica changed to A=2970321. Azimuth stars Zuben-el-Genubi changed to A=2730171. Azimuth stars Antares changed to A=2710031. Azimuth stars Rukbat changed to A=170171. Azimuth star Algedi changed to A=800001. Azimuth stars Sadalmalek changed to A=170171.
Keywords: Zodiac stars, Alshira, Hamal, Aldebaran, Castor, Acubens, Regulus, Spica, Zu- ben-el-Genubi, Antares, Rukbat, Algedi, Sadalmalek